Plan estratégico para el mejoramiento de los servicios educativos del área técnica del colegio “San Camilo”, cantón Quevedo, período 2014-2017 - Arechua Briones, Doris Jennifer (2015)
The research work is a quantitative and qualitative study which is to establish the importance of institutional communication in the Educational Unit "San Camilo". The main objective to raise the present work is to involve the authorities, students and teachers in the evaluation of the activities carried out on site, helping to identify problems and opportunities. For this reason it is important to make a strategic plan to help improve educational services and secure the flow of information appropriate for the achievement of corporate goals. In the first chapter the hypothesis mentioned: a design of a strategic plan that would help improve the service offered by the institution. Consider a Training Plan for executives and teachers' Workshops for Students, Parents and monitoring and evaluation thereof which will improve communication. Referring to discusses the research methodology of deductive form and statistical tabulation of the results obtained in order to reach the conclusions from the interview with the authority of the institution. Referred to the type of research which is descriptive: and performed by field observation, using surveys and interviews. In the fourth chapter, the procedure and data analysis was performed using the following steps: gathering information through surveys and interviews, tabulation of data and analysis of results, analysis of the interview with the authority of the campus, implementation of the strategy and SWOT matrix, development of conclusions and recommendations. The final proposal of the "Design of a Strategic Plan to improve institutional communication in the teaching - learning process of the Education Unit" San Camilo "is presented through the model of Strategic Planning Education, following the sequence of the respective moments that make mention in the theoretical framework, the same as after performing the strategic diagnosis allowed to consider the mission, political vision, objectives and strategies that will allow through the actions reach the goals set with the strategic plan. The defined model was achieved with the objectives in the strategic plan. By studying SWOT, it has been noted strengths, weaknesses, opportunities and threats.